Corrections to “Artificial Hummingbird Optimization Algorithm With Hierarchical Deep Learning for Traffic Management in Intelligent Transportation Systems” - Abdulrahman Alruban; Hanan Abdullah Mengash; Majdy M. Eltahir; Nabil Sharaf Almalki; Ahmed Mahmud; Mohammed Assiri (IEEE Access)
Presents corrections to the paper, Corrections to “Artificial Hummingbird Optimization Algorithm With Hierarchical Deep Learning for Traffic Management in Intelligent Transportation Systems”.